Hyperhomocysteinemia as a predictor of organ-targets subclinic damage in hypertensive patients - Maganty, V.; Vizir, V. A.; Візір, Вадим Анатолійович (Запорізький державний медичний університет, 2018)
Introduction: Arterial hypertensionis one of the most spread uninfectious pandemia over the world, which is presented as a basic reason ofmorbidity, mortality and disabilityas well in adult population. There are a number of criterias for evaluating the cardiovascular risk level. Among them it’s widely discussed the prospects for the study of organ-targets subclinic defeats. As a result, increasing of intima-media thickness seems to be an important component of vascular remodeling in hypertensive patients. It’s well known that both initiation and progression of hypertension are closely associated with the presence of different risk factors, including metabolic, which can be modified, for example - hyperhomocysteinemia. Aim: This study is devoted to definition of the relationship between homocysteine plasma level and vascular remodeling processes in patients with arterial hypertension. Material and methods: According to the aim of the study we have examined 96 hypertensive patients with ultrasound scanning of extracranial part of brachiocephalic arteries (in way to counting the intima-media thickness (IMT) of common carotid arteria (CCA). Homocysteine (HC) plasma level was defined by enzyme-linked immunosorbent assay method.
Keywords: тези доповідей